Peter von Danzig - Możejko, Beata, author.
1 online resource
Keywords: This study traces the chequered history of Peter von Danzig , a French caravel which was inadvertently taken over by Gdańsk (Danzig). Beata Możejko charts the fluctuating and often dramatic fortunes of the caravel, from her arrival in Gdańsk as a merchantman in 1462 to her demise near La Rochelle in 1475. The author examines the caravel’s role as a warship during the Anglo-Hanseatic conflict, and her most famous operation, when she was used by Gdańsk privateer Paul Beneke to capture a Burgundian galley with a rich cargo that included Hans Memling’s Last Judgement triptych. Using literary and archival sources, Możejko provides a comprehensive overview and analysis of the information available about the caravel and her colourful career.